Feasibility, acceptablility and effectiveness of an electronic sensor bed/chair alarm in reducing falls in patients with cognitive impairment in a subacute ward - Wong Shee, A.; Phillips, B.; Hill, Keith; Dodd, K. (Wolters Kluwer Health: Lippincott Williams & Wilkins, 2014)
Falls from bed are common in subacute hospital settings, particularly for patients with cognitive impairment. This repeated measures, single cohort study in 1 subacute ward evaluated effectiveness of an electronic sensor alarm in reducing falls in patients (n = 34) with cognitive impairment. Nursing staff feedback (focus group, survey) was used to determine electronic sensor alarm feasibility. The electronic alarm system was found to be a feasible, effective, and acceptable fall prevention strategy for patients with cognitive impairment.